ANALISIS RESIKO DEMAM THYPOID PADA PASIEN DEWASA DI RSUD LABUANG BAJI MAKASSAR - Muhammad Risal (Stikes Graha Edukasi Makassar, 2019)
The aim of the study: to analyze the risk of typhoid fever in adult patients at the Labuang Baji Regional General Hospital in Makassar. Method: The study used was analytic observational with a case control study design with a sample size of 80 people consisting of 40 control groups and 40 case groups by comparison. Data analysis used was univariate, bivariate and multivariate analysis. Results: The bivariate analysis showed that low education had a 4 times greater risk of developing typhoid fever (OR = 4,333), lower socio-economic risk 3 times more likely to experience typhoid fever (OR = 3,857), individual hygiene was less well risked 4 times greater typhoid fever (OR = 4,889), food sources at risk 6 times more likely to have typhoid fever (OR = 6,231), clean water facilities do not meet the requirements 3 times more likely to experience typhoid fever (OR = 3,115), feces disposal facilities do not meet the requirements 4 times more likely to experience typhoid fever (OR = 4,864). With the results of multivariate analysis with multiple logistic regression tests, it was shown that respondents who had poor personal hygiene risked 7.821 times compared to respondents with good personal hygiene. Discussion: Thypoid fever is a contagious infectious disease caused by the bacterium Salmonella typhidan is still an endemic disease in Indonesia. WHO estimates that the number of typhoid fever cases in the world reaches 16-33 million with 500-600 thousand deaths each year. Conclusion: low education, low socio-economic level, poor personal hygiene, food sources, clean water facilities do not meet the requirements, facilities for disposal of feces do not meet the requirements are risk factors for the incidence of typhoid fever. Suggestion: Research suggests that the community can maintain environmental cleanliness and improve clean living habits in daily life to prevent transmission of typhoid fever